DEVELOPMENT OF TEACHING MATERIALS INTEGRATED MATHEMATIC REASONING ABILITY WITH RELIGIOUS VALUES OF MADRASAH ALIYAH STUDENTS - Cecep Anwar; Hamdan Sugilar; Ujang Dedih; Rohmat Mulyana Sapdi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The limited integrated mathematics teaching materials focusing on discussing reasoning are one in learning mathematics problems, especially in preparation for integrated mathematics Olympiads. This study aimed to develop teaching materials for mathematical reasoning abilities integrated with religious values and students' attitudes towards mathematics integrating religious values. This research method is the ADDIE model development research method. At the implementation stage, the teaching materials were tested on research samples from MAN in the Regency and City of Sukabumi, with 76 students as research subjects. The sampling technique was purposive sampling—implemented through the Schoology application. The study results are as follows: teaching materials in integrated mathematical materials and questions to improve critical, creative, and adaptive reasoning skills towards religious values have good results and need to be developed more broadly than various materials with the separate presentation of mathematical material, teaching materials can improve critical, creative, and adaptive reasoning abilities with good results with an average score using module 60 and without module 52 with a maximum score of 100. Students' attitudes towards learning this integration method are in a suitable category. Integrated mathematics learning provides new experiences for students because learning mathematics is accompanied by learning to understand the contents of the Qur'an verses.